A bioeconomic approach to sustainable development: Incorporating ecological thresholds within intergenerational efficiency. (15th December 2019) - Bithas, Kostas
Abstract: The sustainability debate among economists, and between economists and other scholars, has long been dominated by monolithic approaches, which inhibit policy relevance and social influence. At the same time, certain sustainability policies usually lack a theoretical foundation, a fact that makes policy design and evaluation a fragmented process. Here, we delineate an axiomatic approach for sustainability, which incorporates functionally, within the science of economics, operational elements from biology and ecology. To this end, sustainability is defined on the basis of intergenerational efficiency, maximization of intergenerational welfare, whereas the welfare potentials of future generations are explicitly taken into account and assigned equal importance with those of the current generation. This paper focuses on the dependency of intergenerational efficiency on the natural capital and attempts to define the natural capital that is necessary for ensuring efficiency. We indicate that intergenerational efficiency necessitates the preservation of biological integrity as well as the healthy functioning and resilience of ecosystems. In order to make these conditions operational, we prove that the preservation of crucial biological–ecological threshold arises as the necessary condition for intergeneration efficiency. The operational concept of threshold can be incorporated within economic analyses and inspire sustainability design without the need of assigning fugacious prices to biological assets and services.